Peculiarities of the Russian ballet at the end of the XIXth century - T.V, Portnova (Opción, 2019)
The study aims to investigate peculiarities of the Russian ballet at the end of the XIXth century - beginning of the XXth century in the plastic of small forms via comparative qualitative research methods. As a result, Russian Seasons became a sort of culmination in the exchange of cultures between Russia and Europe and a kind of bridge into the future for Russian art. In conclusion, ballet iconography is one of the most important branches of theater science, the science dealing with graphic material that reflects certain aspects of dance performance.